Muslimani v Sloveniji v primerjavi z drugimi evropskimi muslimani - Jeglič, Urška (Bogoslovni vestnik, 2025)
Slovenia is heavily dominated by indigenous European Muslims who belong to the Hanifi school of law and have their roots in the Balkans – most of them in Bosnia and Herzegovina. The author of the article concludes that Muslims in Slovenia form a distinct group of Muslims in Europe, characterised by a common history, cultural similarities, language and educational structures. The article presents a newly formulated typology that divides Muslims in Slovenia into consistent, cultural and marginal believers.
Keywords: integracija; integration; Islam in Europe; Islam in Slovenia; islam v Evropi; islam v Sloveniji; tipologija muslimanov v Sloveniji; typology of Muslims in Slovenia